Pengaruh 2,4-D (Asam Diklorofenoksi Asetat) dan BAP (Benzyl Amino Purin) terhadap Proliferasi Kalus dan Produksi Metabolit Sekunder dari Kalus Kencur (Kaemferia galanga L.) - Anis Shofiyani; Neni Damajanti (JURNAL ILMU KEFARMASIAN INDONESIA, 2017)
The aim of this research is to fi nd combination of 2,4-D (diclorophenoxy acetic acid) and BAP (benzyl amino purine) concentration which give the best infl uence to callus proliferation and to know the effect of interaction between 2,4-D and BAP to obtain good growth culture of Kaemferia galanga L callus and able to produce secondary metabolite. The design used for callus proliferation was a combination of 2.4 D (1–3 mg/L) and BAP (0-0.2 mg/L). All were randomly arranged in a complete randomized design (RAL) with three replicates, and each treatment unit used 10 bottles of culture. The combination of eff ective treatment for callus proliferation was 2,4 D concentrations of 1 to 3 mg/L and without the addition of BAP (B0). 2,4 D with 1 mg/L concentration gave the best callus proliferation rate indicated at callus volume, fresh weight of callus, dried weight callus and the weakness high and white light colour with friable nature. The higher concentration of 2.4 D to 3 mg/L in the formation of callus color to green and on the process of organogenesis (shoot and root formation). Based on qualitative analysis test using thin layer chromatography (TLC), extract methanol callus Kaemferia galanga research results contain secondary metabolite compounds in the form of alkaloids, flavonoids, tannins, saponins, steroids and ethyl para-methoxycinnamate.